Hubungan Penggunaan Rekam Medik Elektronik dengan Kepuasan Perawat - Dinda Pradita; Nidya Aryani (Sekolah Tinggi Ilmu Kesehatan Panca Bhakti, 2026)
The current developments in the healthcare sector, particularly regarding the application of information in hospitals—especially in medical records—are becoming increasingly rapid with the adoption of Electronic Medical Records. User satisfaction is one of the methods used to measure the extent to which an information system is successful and effective. The 2022 Government Agency Performance Accountability Report notes that out of 3,027 hospitals in Indonesia, only 345 have implemented EMRs. Bhayangkara Hospital as an RME user still faces obstacles where the hospital network often experiences disruptions, thus affecting the effectiveness of staff in working. This study aims to determine the relationship between the use of electronic medical records and the satisfaction of inpatient nurses. This is a quantitative study using a cross-sectional approach, conducted in the Inpatient Ward of Bhayangkara Hospital, Lampung Regional. The population was 76 inpatient nurses and the sample was 43 people, the instrument used was a questionnaire, normality test and data analysis using Spearman Rank. The results of the normality test were that the data were not normally distributed and the results of the Spearman Rank analysis obtained a Sig (2-tailed) value of 0.000 <0.05 and a correlation value of 0.703, meaning that there was a significant relationship between the variables of EMR Use and Nurse Satisfaction at Bhayangkara Hospital. This research is expected to be used as evaluation material for improving health facilities and contribute to supporting the improvement of nurse competence through education and training related to RME.